Post-intervention minimal stent area as a predictor of target lesion revascularization after everolimus-eluting stent implantation for in-stent restenosis: a single-center observational study. Issue 6 (September 2019) - Fujita, Takanari; Takeda, Teruki; Hano, Yoshifumi; Takashima, Noriyuki; Yamaji, Masayuki; Sakaguchi, Tomoko; Maeda, Keiko; Mabuchi, Hiroshi; Murakami, Tomoyuki; Morimoto, Takeshi; Kimura, Takeshi
Abstract : Background: Everolimus-eluting stent (EES) is effective for treating in-stent restenosis (ISR). However, the long-term incidence of target lesion revascularization (TLR) is unknown. Further, the role of post-intervention minimal stent area (MSA) measured by intravascular ultrasound (IVUS) in TLR is unknown in this setting. Patients and methods: Overall, 223 ISR lesions (192 patients) that were treated with EES between 2010 and 2016 were analyzed retrospectively. Lesions were divided into two groups according to the post-intervention MSA [ ⩽ 5.3 mm 2 : 72 lesions (67 patients), and > 5.3 mm 2 : 151 lesions (138 patients)]. The cut-off point was determined on the basis of receiver operating characteristic curve analysis. Results: The cumulative 5-year incidence of TLR was significantly higher in the group with MSA of 5.3 mm 2 or less than in the group with MSA more than 5.3 mm 2 (15.8 and 7.2%, P = 0.01). After adjusting for confounders, the excess risk of the group with MSA of 5.3 mm 2 or less relative to the group with MSA more than 5.3 mm 2 for TLR remained significant [hazard ratio: 3.07, 95% confidence interval (CI): 1.17–8.51, P = 0.02]. Using multivariate logistic regression analysis, we identified female sex (odds ratio: 2.39, 95% CI: 1.06–5.49, P = 0.04) and stent size of 3.0 mm or less (odds ratio: 13.43, 95% CI: 6.23–32.38, P < 0.0001) as independent predictors of MSA of 5.3 mm 2 or less. Conclusion: EES implantation for ISR was associated with an acceptable rate of TLR through long-term follow-up. Postintervention MSA of 5.3 mm 2 or less was associated independently with a higher risk for TLR. Abstract : The role of post-intervention minimal stent area (MSA) measured by intravascular ultrasound (IVUS) in target lesion revascularization (TLR) is unknown after stenting for in-stent restenosis (ISR). 223 ISR lesions treated with everolimus-eluting stents were analyzed retrospectively. Lesions were divided into 2 groups according to the postintervention MSA (⩽5.3mm 2 : 72 lesions, and >5.3mm 2 : 151 lesions). The cut-off point was determined based on receiver operating characteristic curve analysis. The cumulative 5-year incidence of TLR was significantly higher in the MSA ⩽5.3mm 2 group than in the MSA >5.3mm 2 group (15.8% and 7.2%, P=0.01). After adjusting for confounders, the excess risk of the MSA ⩽5.3mm 2 group relative to the MSA >;5.3mm 2 group for TLR remained significant (HR: 3.07, 95% CI 1.17-8.51, P=0.02). Using multivariate logistic regression analysis, we identified female sex (OR 2.39, 95%CI 1.06-5.49, P=0.04) and stent size ⩽3.0mm (OR 13.43, 95%CI 6.23-32.38, P<0.0001) as the independent predictors of MSA ⩽5.3mm 2 .